(untitled) (Bangladesh Journal of Botany, 2018)
The effects of humic acid (HA) pretreatment on the seed germination, seedling growth and leaf anatomy of barley under both normal and saline conditions were studied. HA application partly reduced the final germination percentage, coleoptile percentage, radicle lenght, radicle number and fresh weight of barley germinated under normal conditions while it showed statistically the same effect as the control on the coleoptile length. In parallel with concentration rise, salt inhibited the seed germination and seedling growth of barley. The inhibitive effect of salt on the seed germination and seedling growth was alleviated in varying degrees by HA pretreatment. Moreover, salinity of the medium caused changes in the leaf anatomy of seedlings. HA affected in different degrees the various parameters of leaf anatomy of barley seedlings grown in both normal and saline conditions, and this difference was statistically important.